Conselheiros do Orçamento Participativo nas franjas da sociedade política - Romão, Wagner De Melo [UNESP] (CEDEC, 2011)
This article suggests the need for change in focus of studies on new instances of participation in public policy management, which emerged in the Brazilian re-democratization. Moving away from the literature that addresses the role of civil society in these instances, the author reviews studies on Participatory Budgeting (PB) indicating how such experiences are marked by the dynamics of political society. The argument is reinforced by the presentation of a survey of PB counselors in Osasco-SP, by which we perceive, in general, a role filled by political processes of representative democracy. Most councilors compose the fringes of the political society, lie on the rise in, seeking better position in the local political field, internal disputes within the parties and the municipal government. This points the limits of the democratizing potential of the PB, since the expansion of participation in budget decisions would be just within the political society.

Este artigo sugere a necessidade da mudança de enfoque dos estudos sobre as novas instâncias de participação na gestão de políticas públicas, surgidas na redemocratização brasileira. Afastando-se da literatura que preconiza o papel da sociedade civil nessas instâncias, são revistos os estudos sobre o Orçamento Participativo (OP) que indicam como tais experiências são marcadas pelas dinâmicas da sociedade política. O argumento é reforçado pela apresentação de pesquisa realizada junto a conselheiros do OP de Osasco-SP, pela qual se percebe uma atuação permeada pelos processos políticos próprios da democracia representativa. A maioria dos conselheiros compõe as franjas da sociedade política, situam-se em ascensão a ela, buscando melhor posicionamento no campo político local, no âmbito das disputas internas aos partidos e ao governo municipal. Apontam-se, então, os limites do potencial democratizante do OP, pois a ampliação da participação nas decisões sobre o orçamento se daria apenas para dentro da própria sociedade política.
Participatory budgeting counselors in the fringes of political society
Keywords: Participatory Budgeting; political society; civil society; participation; local government; Orçamento Participativo; sociedade política; sociedade civil; participação; governo local